2016
DOI: 10.29244/jitkt.v7i2.11025
|View full text |Cite
|
Sign up to set email alerts
|

HABITAT QUALITY MUD CRAB (Scylla serrata) IN MANGROVE ECOSYSTEM OF BINTAN BAY, BINTAN DISTRIC, RIAU ISLANDS

Abstract: Mud crab (Scylla serrata) is one of small scale fisheries commodity that have high economic value and typically associated with good mangrove ecosystem. A habitat degradation will cause a serious impact on the existence of mud crab population. The puropse of this study was to assess the ecological quality of mud crab habitat condition on Bintan Bay’s mangrove ecosystem. Ecological data collection was conducted by using plots line transect for mangrove and the mud carb data collection by using fishermen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…In terms of size the crabs collected from Kahayan Delta was smaller than that from Tibi Island. This phenomenon might be caused by the discrepancies of habitat conditions in both locations (Tahmid et al 2015a(Tahmid et al , 2015b. Similar result was also found in east Kutai (Wijaya et al 2010), that have crabs size smaller than in mangrove habitat or the sea.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of size the crabs collected from Kahayan Delta was smaller than that from Tibi Island. This phenomenon might be caused by the discrepancies of habitat conditions in both locations (Tahmid et al 2015a(Tahmid et al , 2015b. Similar result was also found in east Kutai (Wijaya et al 2010), that have crabs size smaller than in mangrove habitat or the sea.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Setiawan and Triyanto (2012) showed that the Scylla serrata mangrove crabs prefer mangrove forests dominated by the mangrove genus Rhizophora. A study by Tahmid et al (2015) also showed a positive correlation A B between mangroves' density and Scylla serrata's abundance. Based on their observations, mud crabs tended to live in the mangrove vegetation with dense root systems capable of holding more silt substrate and forming small caves to hide and food.…”
Section: Discussionmentioning
confidence: 87%
“…The lowest temperature is 31.7 o C, and the highest is 32.7 o C. The water temperature of the research location is not significantly different, and this is probably due to the location of the mangrove vegetation, which is entirely in direct contact with the sea, except in Tanjung Buku, Mapillli District, which is located slightly deeper and surrounded by cultivated water areas but still affected by tidal movements of seawater. According to Karim (2013), a suitable temperature for mud crab cultivation ranges from 26-32 o C. However, according to Tahmid et al (2015), the temperature range of 25-35 o C is still suitable habitat for adult crabs. Thus, the water temperature conditions of the research location are ideal for the maintenance of silvofishery mud crabs because adult crabs are cultivated, so an excess temperature of 0.7 0 C from the suitability threshold is considered not to interfere with crab growth.…”
Section: Discussionmentioning
confidence: 99%